2005
DOI: 10.1123/rsj.29.1.22
|View full text |Cite
|
Sign up to set email alerts
|

A Student Perspective of Intramural Sport Risk Management Procedures

Abstract: One of the best ways for an intramural sports program to ensure that an ordinary and reasonable standard of care is adhered to, as well as guarding against litigation, is communication of a risk management program. While having a risk management plan has been widely stressed, no previous research has been conducted from a participant's viewpoint. Thus, the purpose of this study was to determine the effectiveness of university intramural risk management plans from the participant's perception. The primary resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…White and Cardinal (2004) indicated that programs may not be protected from liability due to injury unless the participant fully comprehends what they are signing. Although a properly developed and implemented waiver may assist in decreasing the potential for litigation, failure to properly communicate its purpose can severely limit its effectiveness (Miller, Veltri, & Gillentine, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…White and Cardinal (2004) indicated that programs may not be protected from liability due to injury unless the participant fully comprehends what they are signing. Although a properly developed and implemented waiver may assist in decreasing the potential for litigation, failure to properly communicate its purpose can severely limit its effectiveness (Miller, Veltri, & Gillentine, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A great deal has been written in recent years in the professional and popular literature regarding risk management, legal liability, and participation in a wide variety of physical activities and sports. There have also been a number of publications and studies dealing with the need for risk management planning in a variety of institutions and organizations (Clement, 1988;Koehler, 1988;Lee, 1999;Mulrooney, Styles, & Green, 2002;McGregor & MacDonald, 2000;Miller, Veltri, & Gillentine, 2005;Miller & Veltri, 2003;Mulrooney & Green, 1997;Risk Management for Campus Recreation, 2007;Sharp, 1990;Stier, 2008;van der Smissen, 1990;Veltri, Miller, & Scott, 2001;White & Cardinal, 2003). However, there has not been a comparable contribution relative to the areas of risk management and legal liability in the area of collegiate/university intramural activities such as this research effort attempted to accomplish.…”
Section: Related Literaturementioning
confidence: 99%